2021
DOI: 10.2991/assehr.k.211110.068
|View full text |Cite
|
Sign up to set email alerts
|

School Leadership Strategies in the Digital Era

Abstract: Leadership is one of the most important components in running an organization. Along with the rapid development of technology, leaders must have a strategy in carrying out their organization in order to achieve the expected goals, especially in the era of the industrial revolution 4.0. How the strategy that need will determine the fate of the school he leads. This study aims to determine how the principal's strategy in the digital era 4.0. This study used a qualitative approach and then it described in a narra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The ideal digital leadership is leadership that follows the industrial revolution 4.0 [44]. The school's leadership strategy in the digital age is that in addition to being a leader capable of using technology, he must also be a visionary, designer, influencer, supporter, and trendsetter for those around him.…”
Section: Resultsmentioning
confidence: 99%
“…The ideal digital leadership is leadership that follows the industrial revolution 4.0 [44]. The school's leadership strategy in the digital age is that in addition to being a leader capable of using technology, he must also be a visionary, designer, influencer, supporter, and trendsetter for those around him.…”
Section: Resultsmentioning
confidence: 99%
“…Hamzah, Nasir and Wahab (2021) asserted that the level of principals' digital leadership and teachers' digital teaching practice both positively correlated at a high level, and it can also improve students' academic performance. Nababan, Zainuddin, Purba,Batu and Sianipar (2021) suggested that since principals are the main actors responsible for managing inputs, processes, and outputs based on government education policies, they can strategically position administrative activities to favour digitalization by: Providing vision and creating opportunities and potentials for evolution of digital activities in school; Designing and supervising school activities that promote digitalization in line with best practices for the 21st century.…”
Section: Provision Of Digital Leadership In Management Of School Heal...mentioning
confidence: 99%
“…Thus, the roles of education leaders in promoting postdigitalization is pivotal. Nababan et al (Nababan et al, 2021) highlights five (5) roles of education leaders in the digitalization of education as: being visionaries, designers, influencers, motivators and trendsetters. By visionaries, the opportunities and potentials embedded in the digitalization of education must be seen by education leaders regardless of the problems that may be associated with such.…”
Section: Theme 3: Roles Of Education Leaders In the Digitalization Of...mentioning
confidence: 99%